Angiolymphoid Hyperplasia With Eosinophilia - Dadapeer H J; Janaki C; Sentamilselvi G; Janaki V R (Wolters Kluwer Medknow Publications, 2002)
A case of angiolymphoid hyperplasia with eosinophilia is reported here with clinical and pathological features.